Influence of load frequency and corrosive environments on fatigue behavior of as-extruded Mg–Zn–Zr–Nd alloy - Wenchao Hu; Wanyi Huang; Ying Sun; Wen Zhang; Lili Tan; Song Zhang; Guangcai Ma; Dan Zhang; Qiang Wang (Journal of Materials Research and Technology, 2023)
Fatigue resistance is a key criterion for new material that would be applied as an implant. As a “smart” implant material with good biodegradability and high strength, Mg–2Zn–0.5Zr–0.5Nd alloy has been recognized as a promising candidate for bone implant. A series of tests on fatigue properties of extruded Mg–2Zn–0.5Zr–0.5Nd alloy are carried out in this study. Alternating cyclic dynamic loads at frequencies of 5 Hz and 10 Hz both in air and in 0.9 wt% NaCl solution were loaded on extruded Mg–2Zn–0.5Zr–0.5Nd alloy respectively. In air condition, the fatigue life variational trends of Mg–2Zn–0.5Zr–0.5Nd alloy at different frequencies are similar according to the stress-life (S–N) curves. However, under high fatigue cycles, the lower loading frequency prolongs the loading time of repetitive stresses and reduces the fatigue life of the samples. In 0.9 wt% NaCl solution, the S–N curves under different frequencies show different changing trends due to the synergistic effect of corrosion environment and loading frequency. It is also found that the fatigue resistance of the alloy in 0.9 wt% NaCl solution is poorer than that in air due to the significant promotion of the formation and growth of corrosion pits by the NaCl environment. In addition, according to the fatigue fracture morphology analysis, it can be found that the failed samples show different fracture patterns in air and 0.9 wt% NaCl solution.